Students’ approaches to solving R-FCI tasks observed by eye-tracking method - Kekule, Martina; Viiri, Jouni (Scientia in educatione, 2018)
This study sought to assess the representational format of task options in the representational variant of the force concept Inventory (R-FCI) test, namely its impact on students’ problem-solving approaches. This was done with the help of eye-tracking equipment. 35 high-school students solved four tasks, mainly from the R-FCI test, which sought to assess the student’s understanding of Newton’s 1st and 2nd Law of Motion. As they were trying to solve the problems, their gazes were tracked by TobiiTX300. A comparison between students who provided the correct and incorrect answer was subsequently carried out. The correctly answering students very quickly found the correct solution both in verbal and graph representation. For motion map representation, they usually compared and made decision between two options. The incorrectly answering students did not show any consistent strategy except they paid the least attention to the correct answer. Moreover, two case stud studies of correctly and incorrectly answering students were described.